Оптимизация производительности процесса перегрузки зерна в условиях ограничения типа «аварийная ситуация» - Шестопалов, С. В.; Хобин, В. А. (Видавництво Львівської політехніки, 2011)
The questions of efficiency economic increase of an grain overload processes by line-transport lines at the factories are considered. The purpose was attaining due to of automatic control systems with switched structure which algorithms provide line productivity which is close to limiting - achievable, and prevention of emergency situations.
Keywords: line-transport line; bucket elevator; grain; emergency situation; control; optimization